Multiple Intelligences of Students in SMPN 22 Padang - Kiki Mulyani; Rahmawati Darrusyamsu; Ganda Hijrah Selaras; Rahmadhani Fitri (ATRIUM PENDIDIKAN BIOLOGI, 2019)
Multiple Intelligences (MI) is a theory about intelligence that was triggered by Dr. Howard Gardner, a figure in education and psychology. a person's intelligence suddenly is not measured by the results of a standard psychological test, but can be seen from a person's habits on two things. First, someone's habits solve their own problems (problem solving). Second, a person's habits create new products that have cultural values (creativity). MI-based learning is a learning process in which when the teacher wants to teach a learning material, the teacher teaches according to the tendency of students' learning styles, because in a classroom there are several students who each have different MIs. The intelligence consists of nine levels of intelligence and is known as the Multiple Intelligences (MI) which includes: 1) linguistic intelligence, 2) mathematical-logical intelligence, 3) visual spatial intelligence, 4) physical-kinesthetic intelligence, 5) musical intelligence, 6 ) interpersonal intelligence, 7) intrapersonal intelligence, 8) naturalist intelligence, and 9) existential. Many benefits can be obtained by knowing the level of MI of students, both for schools, teachers, and students themselves. MI for students is also influenced by several factors, including; innate factors; environmental factor; and maturity factors, this maturity factor related with people age.